Sharia Arisan as an Innovation in Islamic Banking: A Normative Legal Approach - Hengki Firmanda; Mahmud Hibatul Wafi; Samariadi; Firdaus; Rahmad Hendra; Mumaddun Khaerudin Salami (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2024)
This research aims to find out the basics of sharia arisan as an innovative Islamic banking product that has a foundation in application and is in accordance with the concept of local wisdom. Specifically, what this research wants to know is how the mechanism of sharia arisan is applied in Islamic banking. This research is a literature research that uses a normative legal approach. This research shows that sharia arisan does not contradict customary law, Islamic law, and the philosophy of the nation, even sharia arisan is very relevant to be used as a means of investment in Islamic banking. This is because sharia arisan is based on three foundations: juridical, philosophical, and sociological. Furthermore, technically, sharia arisan can be applied in Islamic banking by using three contracts, namely mudharabah mustarakah, wakalah, and ijarah.